Early Post-Transplant Red Blood Cell Transfusion Is Associated With an Increased Risk of Transplant Failure: A Nationwide French Study - Gaiffe, Emilie; Vernerey, Dewi; Bardiaux, Laurent; Leroux, Franck; Meurisse, Aurelia; Bamoulid, Jamal; Courivaud, Cécile; Saas, Philippe; Tiberghien, Pierre; Ducloux, Didier (Frontiers in Immunology, 2022)
Background: Red blood cell (RBC) transfusions are frequently required in the early period after kidney transplantation. However, the consequences of RBC transfusions on long-term outcomes are largely unrecognized. Methods: We conducted a French nationwide cohort study involving all 34 French kidney transplant centers. Patients having received a first kidney transplant between January 1rst, 2002 and December 31th, 2008 were identified through the national registry of the French BioMedecine Agency (Agence de BioMédecine). Number and date of RBC transfusions were collected from the national database of the French transfusion public service. The primary endpoint was transplant failure defined as graft loss or death with a functional graft. Results: Among 12559 patients included during the study period, 3483 (28%) were transfused during the first 14 days post-transplant. Median follow-up was 7.6 (7.5-7.8) years. Multivariate analysis determined that post-transplant RBC transfusion was associated with an increased risk in transplant failure (HR 1.650, 95%CI [1.538;1.771] p<0.0001). Both sensitivity and propension score analyses confirmed the previous result. Conclusions: Red blood cell transfusion early after kidney transplantation is associated with increased transplant failure.